Lactic Acidosis as Presenting Symptom of Thiamine Deficiency in Children with Hematologic Malignancy - Lerner, Reut Kassif; Pessach, Itay; Rubinstein, Marina; Paret, Gideon (Journal of Pediatric Intensive Care, 2017)
Thiamine is an essential component of cellular metabolism and its deficiency results in potentially life-threatening events and profound lactic acidosis through anaerobic metabolism. Acute decompensation in thiamine-deficient patients may manifest as neurologic or cardiovascular changes, with severe lactic acidosis as the presenting symptom. We describe two hematological pediatric patients with thiamine deficiency and hemodynamic instability who improved following thiamine supplements. Thiamine levels were inversely proportional to lactic acidosis; specifically, lower thiamine levels were related to higher lactate levels. We recommend that children with hematological malignancies admitted to a pediatric intensive care unit with low blood pressure and lactic acidosis should be considered for thiamine-level screening and receive supplementation accordingly.
Keywords: thiamine deficiency; lactic acidosis; hematologic malignancy